(untitled) (World Bulletin of Education and Learning, 2026)
This article examines the didactic foundations for developing facilitation and mentoring competencies within the framework of the “Future Teacher” concept in contemporary pedagogical education. The study is grounded in the idea that the professional profile of a modern teacher extends beyond subject delivery and increasingly includes the ability to organize learner-centered interaction, support individual educational trajectories, and cultivate collaborative learning environments. Facilitation and mentoring are analyzed as interrelated professional competencies that strengthen reflective practice, dialogic communication, educational leadership, and pedagogical adaptability. The article argues that these competencies should be developed systematically through competency-based curricula, interactive methodologies, reflexive learning tasks, pedagogical modeling, and practice-oriented training. Special attention is given to the didactic principles that ensure the effective formation of such competencies, including subject-subject interaction, continuity of professional growth, integration of theory and practice, contextuality, and personalized support. The paper also highlights the importance of higher pedagogical education institutions in creating conditions for the formation of future teachers who are capable of guiding, supporting, and inspiring learners in diverse educational settings. It is concluded that the “Future Teacher” concept acquires practical significance when facilitation and mentoring are embedded into the structure, content, and methods of teacher preparation.